2018
DOI: 10.1161/jaha.117.007425
|View full text |Cite
|
Sign up to set email alerts
|

Race and Socioeconomic Status Independently Affect Risk of Major Amputation in Peripheral Artery Disease

Abstract: BackgroundBlack race has been shown to be a risk factor for amputation in peripheral artery disease (PAD); however, race has been argued to be a marker for socioeconomic status (SES) rather than true disparity. The aim of this study is to study the impact of race and SES on amputation risk in PAD patients.Methods and ResultsPatients with incident PAD in the national Veterans Affairs Corporate Data Warehouse were identified from 2003 to 2014 (N=155 647). The exposures were race and SES (measured by median incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
117
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(137 citation statements)
references
References 48 publications
(105 reference statements)
8
117
1
2
Order By: Relevance
“…Similarly, low SES has been tied to worse outcomes in cardiovascular disease and even hospital selection in European countries with universal healthcare 5 6. Socioeconomic disparities have important patient level effects, which have been demonstrated using surrogates including race, insurance status and income 7–10. However, community level factors are critical to understand when assessing the impact of SES on clinical outcomes 11 12.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, low SES has been tied to worse outcomes in cardiovascular disease and even hospital selection in European countries with universal healthcare 5 6. Socioeconomic disparities have important patient level effects, which have been demonstrated using surrogates including race, insurance status and income 7–10. However, community level factors are critical to understand when assessing the impact of SES on clinical outcomes 11 12.…”
Section: Introductionmentioning
confidence: 99%
“…Arya et al demonstrated that there is a higher risk of amputation at a younger age when living in a lower socio-economic area. 6 Furthermore, Tunstall-Pedoe et al reported that living in the most deprived areas is associated with a significant increase in cardiovascular risk, an effect equivalent to increasing a person's age by 10 years or attributing them with a diagnosis of diabetes. 19 In addition to morbidity, mortality is also affected by SES as those in less deprived areas of GG&CHB live up to 15 years longer than those in more deprived areas.…”
Section: Discussionmentioning
confidence: 99%
“…There is a higher risk of PAOD related LEA in those of lower socio-economic status, when these comorbidities have been accounted for. 6 PAOD is the most common cause of major LEA, and rates of LEA are 65% higher in areas of low socio-economic status. 4 Only 40% of people who have a LEA will receive a prosthetic limb.…”
Section: Introductionmentioning
confidence: 99%
“…Goodney et al reported an amputation rate of more than 23 per 10,000 Medicare patients with the peripheral arterial disease (PAD) in Florence, South Carolina [6]. Certain factors, such as age, gender, race, co-existing diseases, smoking, and socioeconomic status, among others, have been associated with higher rates of amputation [6,[8][9][10][11][12]. For example, Ciocan et al identified age as a risk factor for amputation [8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ciocan et al identified age as a risk factor for amputation [8]. Arya et al found the race to be independently predictive of major limb amputation in patients with PAD [11]. Ferguson Despite all the advances in medicine and attempts to delay and prevent amputations, the number of amputations remains high.…”
Section: Introductionmentioning
confidence: 99%